Peran Pusat Pembelajaran Keluarga dalam Mencegah Serta Mengatasi Bullying pada Anak di Kelurahan Jagir Surabaya - Aisyah, Farsya Audria; Bataha, Katerina (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research examines the role of the Family Learning Center (PUSPAGA) in preventing and overcoming bullying in children in Jagir Village, Surabaya City. The objectives of this research are: (1) To determine the role of PUSPAGA in preventing bullying among children in Jagir Village, Surabaya. (2) To find out the role of PUSPAGA in overcoming bullying among children in Jagir Village, Surabaya. The research method in this study uses a qualitative approach with descriptive research. From this research, the researchers obtained the results that: (1) PUSPAGA efforts to prevent bullying among children in Jagir Village, include: PUSPAGA goes to school and socializes to the community during RW Hall parenting classes. (2) The efforts used by PUSPAGA to overcome bullying among children in Jagir Subdistrict, Surabaya are divided into three stages, namely, receiving reports, collecting information and providing services.